Clinical Outcomes and Predictive Factors for Failure With Isolated MPFL Reconstruction for Recurrent Patellar Instability: A Series of 211 Reconstructions With a Minimum Follow-up of 3 Years. Issue 6 (May 2019) - Sappey-Marinier, Elliot; Sonnery-Cottet, Bertrand; O'Loughlin, Padhraig; Ouanezar, Herve; Reina Fernandes, Levi; Kouevidjin, Biova; Thaunat, Mathieu
Background: Reconstruction of the medial patellofemoral ligament (MPFL) is widely acknowledged as an integral part of the current therapeutic armamentarium for recurrent patellar instability. The procedure is often performed with concomitant bony procedures, such as distalization of the tibial tuberosity or trochleoplasty in the case of patella alta or high-grade trochlear dysplasia, respectively. At the present time, few studies have evaluated the clinical effectiveness of MPFL reconstruction as an isolated intervention. Purpose: To report the clinical outcomes of isolated MPFL reconstruction in cases of patellar instability and to identify predictive factors for failure. Study Design: Case series; Level of evidence, 4. Methods: A retrospective analysis of prospectively collected data was performed, including all patients who had undergone isolated MPFL reconstruction between January 2008 and January 2014. Preoperative assessment included the Kujala score, assessment of patellar tracking ("J-sign"), and radiographic features, such as trochlear dysplasia according to Dejour classification, patellar height with the Caton-Deschamps index (CDI), tibial tubercle–trochlear groove distance, and patellar tilt. The Kujala score was assessed postoperatively. Failure was defined by a postoperative patellar dislocation or surgical revision for recurrent patellar instability. Results: A total of 239 MPFL reconstructions were included; 28 patients (11.7%) were uncontactable and considered lost to follow-up. Thus, 211 reconstructions were analyzed with a mean follow-up of 5.8 years (range, 3-9.3 years). The mean age at surgery was 20.6 years (range, 12-48 years), and 55% of patients were male. Twenty-seven percent of patients had a preoperative positive J-sign, and 93% of patients had trochlear dysplasia (A, 47%; B, 25%; C, 15%; D, 6%). The mean CDI was 1.2 (range, 1.0-1.7); mean tibial tubercle–trochlear groove distance, 15 mm (range, 5-30 mm); and mean patellar tilt, 23° (range, 9°-47°). The mean Kujala score improved from 56.1 preoperatively to 88.8 ( P < .001). Ten failures were reported that required surgical revision for recurrent patellar instability (4.7%). Uni- and multivariate analyses highlighted 2 preoperative risk factors for failure: patella alta (CDI ≥1.3; odds ratio, 4.9; P = .02) and preoperative positive J-sign (odds ratio, 3.9; P = .04). Conclusion: In cases of recurrent patellar instability, isolated MPFL reconstruction would appear to be a safe and efficient surgical procedure with a low failure rate. Preoperative failure risk factors identified in this study were patella alta with a CDI ≥1.3 and a preoperative positive J-sign.